Formative and Summative Evaluations in Learning Physics: Do They Complement Each Other? - Nur Rasfina, Mahyan; Nor Hayati, Jaya; Liyana, Rosli (Human Behavior, Development and Society, 2020)
A correlational study was conducted to analyse the relationship between students’ performance in problem-based learning (PBL) and final exam scores with two student cohorts. This study focused on PBL as a teaching strategy and how it related to the students’ achievement in the final exam of a physics course. Exam reliability was assessed by Cronbach’s alpha, and values were obtained ranging from .71 to .83. Correlation between students’ scores in PBL and the final exam was analysed using Pearson’s correlation coefficient. Statistical significant was shown only for semester 2 in Cohort A. For Cohort A semester 1 and both semesters for Cohort B, the correlations were not significant. The corresponding highest Pearson correlation coefficient was .19, which was only for Cohort A semester 2. Coefficients of determination showed that PBL accounted for about 0 to 3.7% of the variance in students’ final exam scores. In all semesters for both cohorts, the difference between final exam scores and PBL scores was significantly higher in the upper quartile of students’ scores, and lower in the lower quartile of students’ scores. Thus, this study showed that PBL can be implemented as one of the teaching strategies to improve some students’ academic achievement.